Hungary : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
The two legs that have held up the forint in recent years-a strong 'EU accession effect' and positive sentiment toward emerging markets-may no longer be strong enough to offset Hungary's weak fundamentals. Fiscal consolidation efforts should be supported by stronger budget controls and greater transparency and accountability. This paper is an effort to shed light on Hungary's employment dynamics, placed in the European Union (EU) context. Hungary's employment generation has been relatively strong, partly owing to the country's favorable initial employment distribution across sectors.